Pengaruh Penambahan Abu Sekam Terhadap Kuat Tekan, Daya Serap Air, dan Kinerja Termal pada Bata Beton - Muhammad Akmal Rusmawan; Shifa Fauziyah; Hartono Hartono (Universitas Diponegoro, 2024)
Bricks are widely used in construction due to their affordability and ease of production, but traditional bricks pose environmental challenges. This study explores improving brick quality by adding rice husk ash (RHA). Two types of bricks, solid and perforated (37 x 15 x 9 cm, with 4 x 7 cm perforations), were tested with RHA additions of 0%, 5%, 10%, 15%, and 20%. Tests included water absorption, compressive strength, and thermal conductivity at 21 days. The results showed that adding up to 10% of RHA significantly improved compressive strength and water absorption. The 10% variation gave the best compressive strength: 4.74 MPa for solid bricks and 4.56 MPa for perforated bricks. However, adding more than 10% reduced strength. The 5% RHA variation had the lowest water absorption, 1.95% for solid bricks and 1.93% for perforated, making it ideal for applications requiring water resistance. Bricks with 20% RHA demonstrated the best thermal performance, reducing temperature rise by 8.23°C in solid bricks and 8.00°C in perforated bricks. The 20% variation also lowered production costs, making it the most economical option. In conclusion, RHA is an effective additive for improving brick quality, with 10% RHA being optimal for strength and water resistance and 20% RHA for thermal performance and cost efficiency.